#TITLE_ALTERNATIVE# - Hidayat (NIM : 233 99 003), Ariya
Abstract: Nowadays, fiber optic transmission system using Dense Wavelength Divison Multiplexing (DWDM), in which up to 80 channels can be transmitted at once, is capable to deliver high capacity transmission. Each information channel is modulated with a different wavelength. As the channel spacing becomes narrower and higher channel power is required to reduce noise and extend transmission distance, the transmitted signal will undergo some degradation, such as a decrease in OSNR (optical signal-to noise ratio), dispersion and various crosstalk. One possible cause of this degradation is the fiber non-linear effects: FWM (four-wave mixing), SRS (stimulated Raman scattering), SBS (stimulated Brillouin scattering), to name a few. The objective of this research is to develop an integrated measurement system which is able to perform a few signal quality parameters: the optical spectrum, OSNR, electrical spectrum, Q factor, and BER (bit error rate). Such a measurement system is expected to function in any existing fiber transmission system without much setup effort and could be operated easily. Measurement of signal quality parameters was performed using three different instruments, i.e. OSA (optical spectrum analyzer), EAS (electrical amplitude sampling) and ESA (electrical spectrum analyzer). A few supporting components are also required, such as optical amplifiers, power meters, DCF (dispersion compensating fiber) and optical switches. Using the related software written in LabVIEW, this system could be operated to perform automatic measurements. The system was tested to measure signal quality of a transmission system where 39 channels (between 1530 nm and 1570 nm, 0.75 nm spaced) are simulated to have FWM effect. The optical spectrum showed two noise channels between 1540.55 nm and 1542.17 nm, caused by three neighbouring channels, and an additional noise was detected close to 1570 nm, These two facts confirmed that FWM did really occur.